Seismic fragility analysis of the Koyna gravity dam with layered rock foundation considering tensile crack failure. (July 2021) - Tidke, Aniket R.; Adhikary, Shrabony
Highlights: Seismic fragility analysis of the Koyna dam-reservoir-layered rock foundation system was studied. The Conditional Mean Spectrum approach was adopted for the ground motion selection. Fragility curves were plotted based on the Incremental Dynamic Analysis results. Various damage states have been proposed based on tensile crack failure. IM parameters PGA and ASI represents seismic risk better as compared to PGV. Abstract: In the present investigation, the seismic fragility analysis of the Koyna dam-reservoir-layered rock foundation system is performed, considering foundation flexibility. For material non-linearity, the Concrete Damaged Plasticity (CDP) model and Mohr-Coulomb failure model are adopted for dam and foundation, respectively. The finite element modelling takes into account the material flexibility, inertial, and damping properties. For the seismic analysis, ground motions are picked according to the Conditional Mean Spectrum approach. An Incremental Dynamic Analysis (IDA) method is used in which each ground motion is scaled at different intensity levels and directly these ground motions are adopted for the time-history analysis. The ground motion Peak Ground Acceleration (PGA), Peak Ground Velocity (PGV), and Acceleration Spectrum Intensity (ASI) are preferred as an intensity measure (IM) parameter. For the seismic fragility analysis, the tensile crack failure in the dam is considered as a limit state. Analytical fragility curves are plotted for the various vulnerability states of the gravity dam based on the damage indices which are evaluated using crack length and dissipation energy in the dam. Numerical results indicate that the dam with more flexible rock layers is more sensitive against seismic forces; however, the dam with hard rock layers is on the safer side. The crest displacement and heel stress can be viewed as a damage measure (DM) parameter for the IDA method. It is observed that the ground motion PGV shows a distinct result in IDA curves as compared to PGA and ASI. However, in fragility analysis, the seismic risk of a gravity dam can be evaluated better against PGA and ASI as compared to PGV.